Creating the Mediterranean : maps and the Islamic imagination - Kahlaoui, Tarek. (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2018)
In Creating the Mediterranean: Maps and the Islamic Imagination Tarek Kahlaoui treats the subject of the Islamic visual representations of the Mediterranean. It tracks the history of the Islamic visualization of the sea from when geography was created by the Islamic state's bureaucrats of the tenth century C.E. located mainly in the central Islamic lands, to the later men of the field, specifically the sea captains from the fourteenth to the sixteenth centuries C.E. located in the western Islamic lands. A narrative has emerged from this investigation in which the metamorphosis of the identity of the author or mapmaker seemed to be changing with the rest of the elements that constitute the identity of a map: its reader or viewer, its style and structure, and its textual content.